Toward setting public health guidelines for chemicals in indoor settled dust?. (23rd October 2020) - Glorennec, Philippe; Shendell, Derek G.; Rasmussen, Pat E.; Waeber, Roger; Egeghy, Peter; Azuma, Kenichi; Pelfrêne, Aurélie; Le Bot, Barbara; Esteve, Williams; Perouel, Guillaume; Pernelet Joly, Valérie; Noack, Yves; et al.
Abstract: Indoor settled dust may result in substantial human exposure to chemicals, especially by ingestion following hand‐to‐mouth or hand‐to‐object‐to‐mouth contact. As with other environmental media related to exposure, dust may thus be subject to regulation. An international scientific workshop was convened in Paris in September 2019 firstly to assess the relevance for public health of setting guidelines for indoor settled dust, and secondly to discuss scientific and technical challenges related to such guidelines. The main discussions and conclusions, with consensus achieved, are reported herein. Discussions concerned general considerations, objectives and definitions, relevance for a health‐based guideline, units of measure, and finally derivation of the guideline. These points should be addressed when considering an indoor settled dust guideline as part of a policy to reduce exposure indoors to a given chemical or group of chemicals.